Design and Build PLTS On-Grid as Household-Scale Electricity Support - Aripriharta, Ari (Jurnal Kajian Teknik Elektro, 2024)
At present the installation of PLTS in households is one of the government programs as stated in the Minister of Energy and Mineral Resources regulation No.49 of 2018 which contains permits for PLTS installation, independent electricity production and electricity export to PLN. Therefore, a Final Project was created with the title "Design of On-Grid PLTS as a Support for Household-Scale Electrical Power". In this Final Project a 200W On-Grid PLTS has been designed for households with 900 VA electric power. This has been adjusted to PLN rules where the maximum limit for PLTS installation is 100 percent of the connected power. The installation of PLTS On-Grid is expected to save electricity costs by up to 20 percent of normal bills every month. The method used in the design of this On-Grid PLTS uses design and experimentation. The design used online software, namely onshape, while the experiment was carried out for 7 days where data was collected for 6 hours every day in hot, cloudy and drizzly weather, the data taken was adjusted to several parameters such as solar irradiation, light intensity, temperature, voltage, current and power. The measurement results show that the amount of voltage and current generated by the PLTS system decreases as the light intensity decreases. The maximum power that can be produced by PLTS in hot weather is 156W, when the weather is cloudy the maximum power is 73,728W, while the maximum power generated by PLTS in drizzly weather is 24,706W. From the test results, it was also found that the efficiency of the On-Grid PLTS was 16.5% where this system can help meet household load power that is used for approximately 6 hours during the day. In addition, the Root Mean Square Error value for measuring the dc output is 13.13 and the ac output is 14.4. Meanwhile, the BEP (Break Even Point) value or breakeven point for the construction of the On Grid PLTS system with a performance ratio of 93% will be obtained for approximately 9.1 years.